Proceedings of the 21st International Conference on Industrial Engineering and Engineering Management 2014 - Qi, Ershi; Shen, Jiang; Dou, Runliang; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2015)
Being the premier forum for the presentation of new advances and research results in the fields of Industrial Engineering, IEEM 2014 aims to provide a high-level international forum for experts, scholars and entrepreneurs at home and abroad to present the recent advances, new techniques and applications face and face, to promote discussion and interaction among academics, researchers and professionals to promote the developments and applications of the related theories and technologies in universities and enterprises and to establish business or research relations to find global partners for future collaboration in the field of Industrial Engineering. All the goals of the international conference are to fulfill the mission of the series conference which is to review, exchange, summarize and promote the latest achievements in the field of industrial engineering and engineering management over the past year and to propose prospects and vision for the further development.
Application on Product Information Storage of Expanded Linear List Based on Two-dimension Array -- Key Factors of K-nearest Neighbors Nonparametric Regression in Short-time Traffic Flow Forecasting -- The Distribution of Residual Control Rights under Self-interest Behavior -- VPDs Operating System Modeling and Performance Analysis Generalized Stochastic Petri Nets -- Research on Initiative Knowledge Spillovers of Supply Chain Entities Based on Service-oriented Manufacturing -- Study on the Relationship between the Government Dynamic Game -- The Method of Time Synchronization between Telecommunication Base Stations with GPS Common View -- Research on Random Mixed-model Two-sided Assembly Line Balancing Using Genetic Algorithm -- The Capacity Preparation in the Two-period Supply Chain with Remanufacturing Products and IOT -- Utility-Cost Model for Discrete Event Logistics Systems Simulation.
Keywords: Engineering; Engineering economics; Engineering economy; Building -- Superintendence; Construction industry -- Management; Construction superintendence; Engineering; Construction Management; Engineering Economics, Organization, Logistics, Marketing; Electronic books